Methane Activation by Heterogeneous Catalysis - Horn, Raimund; Schlögl, Robert (Catalysis letters, 2015)
Methane activation by heterogeneous catalysis will play a key role to secure the supply of energy, chemicals and fuels in the future. Methane is the main constituent of natural gas and biogas and it is also found in crystalline hydrates at the continental slopes of many oceans and in permafrost areas. In view of this vast reserves and resources, the use of methane as chemical feedstock has to be intensified. The present review presents recent results and developments in heterogeneous catalytic methane conversion to synthesis gas, hydrogen cyanide, ethylene, methanol, formaldehyde, methyl chloride, methyl bromide and aromatics. After presenting recent estimates of methane reserves and resources the physico-chemical challenges of methane activation are discussed. Subsequent to this recent results in methane conversion to synthesis gas by steam reforming, dry reforming, autothermal reforming and catalytic partial oxidation are presented. The high temperature methane conversion to hydrogen cyanide via the BMA-process and the Andrussow-process is considered as well. The second part of this review focuses on one-step conversion of methane into chemicals. This includes the oxidative coupling of methane to ethylene mediated by oxygen and sulfur, the direct oxidation of methane to formaldehyde and methanol, the halogenation and oxy-halogenation of methane to methyl chloride and methyl bromide and finally the non-oxidative methane aromatization to benzene and related aromates. Opportunities and limits of the various activation strategies are discussed. Graphical Abstract .